Pedagogical Foundations of the Technology of Vocational Guidance for Students - Zhaina, Beisenbayeva; Ospan, Sangilbayev; Elmira, Mukazhanova; Gulnar, Kassymova; Tolganay, Bersugirova (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Today, considering professional specialists' needs, the content and technology of training in career counseling from the perspective of practice are not sufficiently developed. Thus, a search for new forms, methods, and means of conducting career guidance with students is necessary. This article offers a broad range of technologies and their optimal combination in career guidance work with pupils in the integrated system “School – University.” A leading approach to the study of this problem is an integrative approach that leads to the necessity to use traditional and innovative technologies that contribute not only to effective assimilation of knowledge but also an early social adaptation of the prospective adolescents to university conditions. The present study consists of a needs assessment of students' career guidance and career counseling programs in the university. The research is based on a survey developed on a sample of 120 students from the Almaty schools. The collected data has been both qualitative and quantitative. The students have been inquired about their professional path, about their career decisions, personal and professional values, abilities and competencies, intentions for the future, etc. The study's most relevant results show that: students are poorly informed about job opportunities, their expectations for the future are not connected with their own knowledge and abilities, they do not have a coherent career plan, and they encounter major barriers in the career decision process. The results are important for career counselors as they can be used to develop career guidance programs in the university environment. Purpose of the research: to theoretically substantiate and experimentally test the pedagogical conditions of vocational guidance for senior schoolchildren in the context of specialized education. The article is valuable for teachers and faculty of educational and vocational institutions to organize and conduct career guidance with students, applicants, and students.